ClpXP and ClpAP control the Escherichia coli division protein ZapC by proteolysis - Buczek, Monika S. (Microbiology (Reading), 2016)
The bacterial FtsZ-ring is an essential cytokinetic structure under tight spatiotemporal regulation. In Escherichia coli, FtsZ polymerization and assembly into the Z-ring is controlled on multiple levels through interactions with positive and negative regulators. Among these regulatory factors are ZapC, a Z-ring stabilizer, and the conserved protease ClpXP, which has been shown to degrade FtsZ protofilaments in preference to FtsZ monomers. Here we report that ZapC and ClpX interact in a protein–protein interaction assay, and that ZapC is degraded in a ClpXP-dependent manner in vivo. The SspB adaptor protein is not required for targeting ZapC to the ClpXP proteolytic machinery. A mutation disrupting the zapC ssrA-like sequence (zapC(DD)) stabilizes ZapC consistent with a reduction in ClpXP-mediated ZapC degradation. ZapC(DD) retains the ability to interact with FtsZ and to promote bundling in vitro indicating that WT ZapC contains discrete FtsZ and ClpX recognition motifs. Additionally, ClpAP complexes are sufficient for degradation of ZapC in the absence of ClpX in vivo. Further, chromosomal expression of zapC(DD) suppresses filamentation of the temperature-sensitive ftsZ84 mutant, confirming the role of ZapC as a Z-ring stabilizer. Lastly, changes in ClpXP and ZapC levels lead to cell division effects, likely through their roles in modulating FtsZ assembly dynamics. Taken together, our results indicate that the Z-ring stabilizer ZapC is a substrate of both ClpXP and ClpAP in vivo. Our data also point to a more complex regulatory circuit that integrates FtsZ, ClpXP and ZapC in achieving Z-ring stability in E. coli and related species.